(NkOORDINACIONNYE SOEDINENIQ METALLOW S KRAUN(B-(NLIGANDAMI (B/s - (NcIWADZE(B, (NaSLAN `SUPOWI^s; (NwARNEK(B, (NaLEKSANDR aLEKSEEWI^s; (NhUTORSKIJ(B, (NwITALIJ eFIMOWI^s ((NmOSKWA (B:s (NnAUKA(B,s, 1991)
(NbIBLIOGR(B. (NW KONCE GLAWs
Keywords: (NkOMPLEKSNYE SOEDINENIQ S METALLAMIs; (NkRAUN(B-(N\FIRYs